1983
DOI: 10.1111/j.1365-3091.1983.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental discrimination based on quartz grain surface textures: a statistical investigation

Abstract: The relative abundance of thirty‐two surface features identified on the surfaces of quartz sand grains from eight coded samples was noted independently by five scanning electron microscopists. These data (reduced to binary form) were the subject of canonical variate analyses which discriminated clearly between all samples. Thirteen variables were important in distinguishing between the eight samples. This indicates that there are no single key surface features which, on their own, would allow rapid environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 8 publications
2
18
0
1
Order By: Relevance
“…The development of quartz grain surface texture types is really a return to the methodology that was employed when the technique was in its infancy, in that when quartz surface texture analysis was undertaken in the 1960s descriptive terminology was used. The introduction of statistical analysis in surface texture studies was introduced in the literature in the 1970s and 1980s [13][19] however, attempts to automate grain texture analysis [20] failed to achieve the hoped-for breakthrough and the time required for preparation and analysis of samples proved unpopular without automation. More recently the designation of quartz gr ain types as presented in the geological literature [14][15] [16][17] has enabled direct comparison techniques to be employed in the forensic arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of quartz grain surface texture types is really a return to the methodology that was employed when the technique was in its infancy, in that when quartz surface texture analysis was undertaken in the 1960s descriptive terminology was used. The introduction of statistical analysis in surface texture studies was introduced in the literature in the 1970s and 1980s [13][19] however, attempts to automate grain texture analysis [20] failed to achieve the hoped-for breakthrough and the time required for preparation and analysis of samples proved unpopular without automation. More recently the designation of quartz gr ain types as presented in the geological literature [14][15] [16][17] has enabled direct comparison techniques to be employed in the forensic arena.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure had merit in that it concentrated the attention of the operator upon the whole variety of textures which could be found on the surface of a grain. Quantitative analysis of the data collected in this manner proved that the eventual diagnosis of grain history was very good, even with inexperienced operators [13]. The problem with this type of quantification was that it only provided a description of the features found on the grain.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…These textures and the frequencies with which they occur, in tul-n, can be used to determine the sedimentary hi\tories of quartz grains. Culver et al (1983) found that this technique. applied by five different analysts to sand grains from thc same eight sedimentary settings, ranging from glaciation to i l l sitll granite weathering, reliably revealed the history of sand grains.…”
Section: Surfizce Textural Analysismentioning
confidence: 99%
“…Po letu 1960 se je uporaba SEM pri prou~eva-nju povr{ine kremenovih zrn za interpretacije izvora, na~ina transporta, sedimentacijskega okolja in diagenetskega razvoja kamnin zelo pove~ala (KRINSLEY & TAKAHASHI, 1962;KRINSLEY & DONA-HUE, 1968;KRINSLEY & DOORNKAMP, 1973;MARGO-LIS & KRINSLEY, 1974;AL-SALEH & KHALAF, 1982;CULVER et al, 1983;CARTER, 1984;in drugi). S SEM so odkrivali nove strukture povr{ine, ki jih je bilo potrebno opisati in poimenovati.…”
Section: Struktura Povr{ine Kremenovih Zrnunclassified